Special health care needs during childhood and academic achievement in secondary school - van Zwieten, Anita; Teixeira-Pinto, Armando; Lah, Suncica; Nassar, Natasha; Craig, Jonathan C; Wong, Germaine (My University, 2021)
Background Secondary education has lifelong implications for wellbeing. We evaluated associations between the duration and timing of special health care needs (SHCN) across childhood and academic achievement in secondary school. Methods Cohort design. The structured modelling approach was used to evaluate life-course models for associations between the duration and timing of SHCN (measured using a two-item SHCN screener across ages 4–5, 6–7, 8–9 and 10–11 years) and Grade 7 (median age 12.5 years) reading and numeracy achievement. Linear regressions were fitted for each life-course model: four critical period models (each including SHCN exposure in one period), one sensitive period model (including SHCN exposure in all periods) and two strict accumulation models (including the duration of SHCN exposure in linear form then categorical form). Interactions of SHCN with child sex and family socio-economic status (SES) were examined. Results Of 3734 children, 1845 were female. The number of children with SHCN was 434 (11.7%), 458 (12.9%), 534 (14.7%), 551 (15.4%) at 4–5, 6–7, 8–9 and 10–11 years respectively. For both outcomes, the linear strict accumulation model fitted best, and interactions of SHCN with sex and SES were non-significant. The average decrease in school achievement z score (95% confidence interval) per period of having SHCN was 0.04 (−0.07 to −0.02) for reading and 0.08 (−0.11 to −0.05) for numeracy. Conclusions A longer duration of SHCN from age 4–11 years has small-sized cumulative associations with poorer Grade 7 reading and numeracy achievement. Each period of SHCN between 4 and 5 and 10–11 years was associated with nearly 0.05 and 0.1 of a standard deviation reduction in Grade 7 reading and numeracy scores respectively, and these associations did not appear to differ across sex or SES. These findings suggest that children with persistent SHCN are at risk of academic deficits and should receive focused interventions.
Child: Care, Health and Development
Keywords: Adolescents and youth; Disadvantage, adversity and resilience; Childhood and child development; Health and wellbeing; Income, wealth and finances; Learning, education and training